2008
DOI: 10.1016/j.plantsci.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Melon, an alternative model plant for elucidating fruit ripening

Abstract: Ethylene perception has been studied using Arabidopsis and tomato as model plants during last two decades. Arabidopsis has been an ideal model system for gene identification and subsequent functional analysis of the identified gene. On the other hand, tomato is not only the model of choice to study climacteric fruit ripening but also crops of agronomic importance and hence has been at the forefront of the comparative analysis with Arabidopsis. A number of fruit development and ripening studies in melon has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 74 publications
0
53
0
3
Order By: Relevance
“…This therefore indicates the existence of different and complex genetic regulation of the climacteric character . In view of the enormous amount of information that has been already accumulated, melon have been suggested as an alternative model system for studying fruit ripening, ethylene perception and signaling in addition to the study material to unraveling the basis of the differences between climacteric and non-climacteric fruit (Ezura and Owino 2008).…”
Section: Fruit Ripeningmentioning
confidence: 99%
“…This therefore indicates the existence of different and complex genetic regulation of the climacteric character . In view of the enormous amount of information that has been already accumulated, melon have been suggested as an alternative model system for studying fruit ripening, ethylene perception and signaling in addition to the study material to unraveling the basis of the differences between climacteric and non-climacteric fruit (Ezura and Owino 2008).…”
Section: Fruit Ripeningmentioning
confidence: 99%
“…In addition, melon fruits also have significant variations in ripening physiology and are categorized as climacteric or nonclimacteric, based on their ripening-related respiration rate and ethylene evolution profiles (Giovannoni 2007). Melon fruit is a potential alternative model to tomato (Solanum lycopersicum L.) for studies of fleshy fruit ripening (Ezura and Owino 2008;Giovannoni 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In cucumber (Cucumis sativus), the major sex expression gene has been isolated (Li et al, 2009). Investigations into the genetic interactions between CmW1P1 and CmACS-7 have indicated that floral sex determination is a complex process involving multiple events (Ezura Owino, 2008). The a/A gene (CmACS-7) encodes an ethylene biosynthesis enzyme CmACS-7 that represses stamen development in female flowers.…”
mentioning
confidence: 99%